Prediction of Informatics Engineering Student Graduation using Naïve Bayes Method - Koten, Antonius Suban; Bouk, Anggela M; Rozi, Fatchulloh Reza Ar; Salisu, Imam Auwal (Lumina Infinity Academy Foundation, 2026)
Student graduation is one of the indicators of the success of the educational process in higher education. This study aims to predict the graduation of students in the Informatics Engineering study program using the Naive Bayes method, by considering the Final Semester Exam (UAS), Mid-Semester Exam (UTS), assignments, and attendance as the main variables. The Naive Bayes method was chosen because of its simplicity in handling multivariable data and its ability to produce accurate classification models.